The formation and mineralization of bone tissue under different regimes of motor activity in the age aspect - Dariya Kozak; Nataliya Davybida (Kazimierz Wielki University, 2015)
Kozak Dariya, Davybida Nataliya. The formation and mineralization of bone tissue under different regimes of motor activity in the age aspect. Journal of Education, Health and Sport. 2015;5(9):700-708. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32374 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A700-708 https://pbn.nauka.gov.pl/works/657914 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   UDC 611.717/.718-018-02:612.766.1]-053   THE FORMATION AND MINERALIZATION OF BONE TISSUE UNDER DIFFERENT REGIMES OF MOTOR ACTIVITY IN THE AGE ASPECT   Dariya Kozak, Nataliya Davybida   SHEI «I. Horbachevsky Ternopil State Medical University of the Ministry of Public Health of Ukraine»   Summary A deep study of the adjustment processes of bone, its structure, chemical composition, adaptive capacity is a necessary condition for clarification of the influence of labor, sports and a number of trades that occur in connection with the scientific - technical progress on the body. The organization and simulation of the different modes of motor activity does not fully meet the training process rights in physical education and sport. However, the results obtained in this pilot study are related to the disclosure of general biological laws based on individual and genetically determined characteristics of individuals, knowledge of which will serve as a morphological substantiation of the training process and prediction of structural changes in the skeleton at various modes of exercise, injury prevention, and the development of osteoporosis. As follows: 1. Intense exercise causes slowdown in growth and osteoclastic resorption of humeri and their structural elements by young and mature animals. By animals with severe senile changes there observed significant destructive changes in all parts of the humeri. Morphometric research methods allow confirming maximal destructive bone changes in the group of senile animals and minimal ones - by mature animals. 2. Inturn, moderate exercise is a deterrent of involute changes in humeri. In the group of young animals there is observed deceleration of the narrowing processes of the growth plate width and increase of osteoblasts activity, what was indirectly manifested in increase of the bones size and their structures by experimental animals. In the group of animals with severe senile changes there was marked slowdown of bone demineralization. It was determined that the effect of the different regimes of exercise on morphogenesis processes depends on age, as well as intensity and duration of exercise. 3. Results of the study have both theoretical and practical importance because they provide methodological basis for the study of adaptive changes in bone system, determining a range of its transformation. Ability to predict training exercises and target use graduated physical exercises with the aim to correct skeletal structural changes depending on age was experimentally confirmed. Keywords: exercise, endurance, macro - micro elements, humerus.